Effects of dietary enzymatic extracts from cellulose digestion of palm kernel cake on growth performance, meat quality and digestibility of broiler chicken - Zamani, Hassan Usman (2015)
Utilisation of palm kernel cake (PKC) is limited in monogastric animal nutrition due to its high fibre content, low lysine and methionine. These factors can be address by supplementation of exogenous enzymes into the diet. Two experiments were conducted for these studies. The first experiment was conducted to produce enzyme and determine their activity. Experiment 2 was carried out to study the effects of different inclusion level of locally produced enzymes on growth performance, meat quality and digestibility of broiler chicken. The experimental design was based on completely randomized design. Three cellulolytic bacteria; Paenibacillus curdlanolyticus DSMZ 10248, Bacillus megaterium ATCC 9885, and Paenibacillus polymyxaATCC 842were used to produce enzyme at different moisture ratio of 1:0.5, 1:1, and 1:1.5. The ratio was later increased to nine ratios; 1:0, 1:0.5, 1:1, 1:1.5, 1:2.0, 1:2.5, 1:3.0, 1:3.5 and 1:4.0. This was done to obtain the optimum moisture ratio needed for the solid state fermentation (SSF). Based on the result obtained, higher enzyme activities were recorded on the fourth day of SSF at moisture of 1:1.5. However, lower enzyme activities were observed at the ratio of 1:0.5. No activity was recorded on the eight day of SSF. PKC and Paenibacillus curdlanolyticus were then chosen as the best raw material and microbe for their higher enzyme activities in order to produce enzymes for the next experiment. A total of 252 male broiler chickens (Cobb 500) were raised in a battery cage system in the research Unit at Department of animal science, Universiti Putra Malaysia, from day-old to 42 days of age. The birds were randomly divided into 7 groups and fed different treatment diets: All diet contain 15% PKC + corn and soybean meal. All the diet contains 15% PKC + corn and soybean meal. The dietary treatment consisted of: (i) PKC without enzyme (ii) PKC + 0.1% commercial enzyme (iii) PKC + 0.2% crude enzyme. (iv) PKC+ 0.4% crude enzyme (v) PKC + 0.6% crude enzyme (vi) PKC+ 0.8% crude enzyme (vii) PKC + 1% crude enzyme. The findings showed that addition of locally produced enzyme to palm kernel cake dietary significantly increased (P<0.05) growth performance of broiler chicken. Higher body weight and feed intake were observed in the groups fed 15 % PKC with 1% crude enzymes, while lower body weight and feed intake were observed in groups fed 15 % PKC without enzymes. Similarly, higher FCR were recorded in the same group. However, the result for meat quality and digestibility showed that birds fed PKC with locally produced enzymes showed an improvement compare to those fed 15% PKC without enzymes. Production of enzymes via solid state fermentation using cellulolytic bacteria in PKC, rice bran and wheat pollard as substrates could be achieved at an incubation time of 4 days at a moisture ratio of 1:1.5. Similarly, application of enzymes into the diet reduces the variation in nutrient quality of ingredients. It also increases the feeding value of raw materials, thereby improving growth performance, meat quality and digestibility of broiler chicken.